Art in adolescent sex education from the viewpoint of university extension - Bárbara Yakelín León Rodríguez.; María Teresa Santana García; Tania Díaz Pérez (Edumecentro)
Introduction: one of the objectives of university extension is to promote cultural development among the different social sectors of the community, focused on socio-humanistic education, and it can play an important role in the sexual education of adolescents through art. Objective: to analyze from several updated bibliographic sources the role played by art assumed from university extension in the sexual education of adolescents. Methods: a review of bibliographic sources was carried out in SciELO, Dialnet and Google Scholar, with the use of keywords: art, university extension, sexual education and adolescents. Scientific articles, undergraduate and master's theses were selected to achieve relevance in the study conducted. Development: the role of art from university extension in the sexual education of adolescents was evaluated conceptually, and the most relevant research was analyzed according to the author, year and type of publication or study carried out. The bibliographic review made it possible to establish criteria and the main regularities in relation to the subject. Conclusions:the review of publications made it possible to confirm the positive effects of art in the sexual education of adolescents from the university extension. This new learning scenario is still a challenge for teachers and researchers to understand.